Positional Deprivation and Support for Redistribution and Social Insurance in Europe. (April 2023) - Burgoon, Brian; Baute, Sharon; van Noort, Sam
We argue that support for redistribution increases when one experiences "positional deprivation, " situations when one's own income increases slower or decreases faster compared to that of others. This specific combination of economic suffering over-time and relative to others has effects beyond well-studied measures of suffering that are static and/or absolute in nature, such as income level. We empirically explore this hypothesis by using "objective-material" measures of positional deprivation derived from the Luxembourg Income Studies and the European Social Survey, and by using "subjective" measures derived from an original survey in 13 European countries. We find that those whose income growth is outpaced by the average and/or richest members of their country are more likely to support redistribution. We also find that the objective and subjective measures of positional deprivation are significantly correlated, and that positional deprivation's fostering of support for redistribution holds above-and-beyond static and/or absolute measures of economic experience.